Background prevalence of subclinical Shiga toxin-producing Escherichia coli in children attending childcare facilities in the Irish Midlands. (16th December 2019) - Burns, H; Fallon, U; Collins, A; Ni Shuilleabhain, C
Abstract: Background: Exclusion of asymptomatic shedders of Shiga toxin-producing Escherichia coli (STEC) from childcare facilities (CCFs) is a recognized measure to minimize risk of secondary transmission. This is predicated on factors including an assumption of low background prevalence of STEC amongst CCF attendees. There is a paucity of scientific evidence regarding the true prevalence of STEC in paediatric populations. The study aimed to develop and test a methodology to estimate background prevalence of STEC amongst CCF attendees at regional level in Ireland. Methods: Computerized Infectious Disease Reporting data were used to compile a list of outbreaks of STEC occurring in CCFs in the Irish Midlands since the introduction of polymerase chain reaction (PCR)-based testing. Laboratory data were used to determine background prevalence of STEC in screened children in each outbreak individually and across all outbreaks. Results: A pooled summary prevalence estimate of 2.9% (95% confidence interval 1.4–5.5%) was determined for the entire screened cohort across all outbreaks. Sensitivity analysis supported the validity of the estimate. Conclusions: The relatively high prevalence estimate of 2.9% suggests that a public health risk assessment approach to return of prolonged asymptomatic shedders to the CCF may be appropriate in peak STEC season in the Midlands.